Evaluation of Simulation Based on the Job Training for Industrial Chemical Engineering Students at SMKN 2 Cilegon - Duwi Lestari; Moh. Fawaid; Suhendar Suhendar (VANOS Journal of Mechanical Engineering Education, 2026)
This study evaluates the simulation-based On the Job Training (OJT) program at SMK Negeri 2 Cilegon as an alternative to Field Work Practice (PKL), developed to address the mismatch between vocational curricula and industry needs as well as the limited availability of industrial internship placements. The evaluation employs the CIPPO model, and data were collected through observations, semi-structured interviews, Focus Group Discussions (FGDs), and document review, with primary and secondary data analyzed using qualitative data analysis techniques. The findings indicate that the context of the OJT program is highly aligned with industry needs. The input aspect is supported by qualified teachers, industry mentors, and adequate student readiness. The process is implemented through structured stages, resulting in products such as equipment SOPs, student reports, and competency certificates, while the outcomes demonstrate improvements in students’ technical competencies, interpersonal skills, and overall work readiness.